Code-Mixing in Malay Composition-Writing Among Chinese Pupils: A Pragmatic Analysis: (Percampuran Kod dalam Penulisan Karangan Bahasa Melayu Pelajar Cina: Analisis Pragmatik) (Jurnal Bahasa, 2016)
This research studies the pragmatics aspect of code-mixing in Malay language composition among the Chinese pupils. The study focuses on two aspects i.e identifying errors in the Chinese pupils' compositions, analysing these errors and finally explaining the aspects of code-mixing in order to understand the pupils' message from the pragmatics perspective, using bridging cross reference analysis. This study was carried out at one tuition center attended by Chinese pupils. A total of 80 pupils were involved in this study. The findings show that the most common errors in Malay language composition-writing are confusion in using affixes, wrong choice of words, using the improper form of personal pronouns, besides common errors such as using abbreviation and incorrect conjunctions. Concerning code-mixing, bridging cross reference was used in order to comprehend the message intended by the pupils. The analysis for code-mixing is divided into two parts: code-mixing for nouns, and for other words (other than nouns). Interestingly, the findings show that even though code-mixing occurred from L1 (Mandarin) and also L3 (English) in a Malay sentence construction, the message can be comprehended using bridging cross reference.Keywords: code-mixing, Chinese pupils, theoretical framework, pragmatics, bridging cross-reference